Rural pharmacy services in Western Australia : a time-series comparative study - Wibowo, Yosi Irawati (Curtin University, 2007)
Objectives: to evaluate rural pharmacy practice in Western Australia (WA) (“2006 data”), and to perform a time-series comparison with the previous data (“2002 data”) that were sourced from the National Pharmacy Database Project in 2002.Methods: a questionnaire used in the 2006 survey was developed based on that used in the 2002 national survey. In the 2002 survey, questionnaires were mailed to 1391 representative participant pharmacies (82 participants from rural WA), of which 1131 were returned (66 respondents from rural WA). The response rate for rural WA was 80.5%. In the 2006 survey, questionnaires were mailed to all 103 sample pharmacies of rural WA, of which 51 were returned. This gave a response rate of 49.5%. Chi-square tests were used to test individual associations between year of survey against pharmacist or pharmacy characteristics, or provision of services. Where significant associations were reported between year of survey and provision of particular services, logistic regressions controlling for gender, age, PhARIA location, and inclusion of a forward pharmacy area, were performed.Results: pharmacist characteristics were not significantly different across the two surveys with regard to age, gender, year of registration, qualification, Continuing Professional Education (CPE) involvement, and position. Similar pharmacy characteristics were reported in relation to PhARIA, setting, group membership, inclusion of counselling areas, method of operation, trading hours and annual turnover. Only Quality Care Pharmacy Program (QCPP) accredited-pharmacies significantly increased. In both surveys, WA rural pharmacies offered a range of services, including prescription-related activities, medication reviews, preventive services, primary health care, harm minimisation services, and Enhanced Pharmacy Services (EPS). A significantly higher percentage of pharmacies provided clinical testing for monitoring, Domiciliary Medication Management Reviews (DMMRs), and printed information for non-prescribed medicines. There were marked increases in weight testing and weight management services. Smoking cessation was offered by over 50% of pharmacies, and tended to increase. However, other EPS (asthma, diabetes, hypertension, hyperlipidaemia), which correspond to the National Health Priorities Areas (NHPAs) and rural needs, were reported by less than 50% of pharmacies in both surveys. A shortage of pharmacy workforce still remained a problem, as evidenced by similar numbers of full-time equivalent (FTE) pharmacists per pharmacy. This study also highlights several issues, including less CPE involvement, low uptake of forward pharmacy, and low participation in the S100 scheme.Conclusions: This study found a remarkable consistency of WA rural pharmacy practice across the two surveys. However, significant increases were reported in some important services such as weight management. This findings may indicate that support for important services is required if they are to be taken up by the profession. The government and pharmacy bodies need to address the workforce barriers to improve access to pharmacy services for rural communities.